Pengaruh Senam Hamil Terhadap Berat Badan Dan Kadar Gula Darah Ibu Hamil Trimester III Di Kota Pekanbaru - Ilda Lindriyani; Rully Hevrialni (Poltekkes Kemenkes Padang, 2019)
The prevalence of gestational diabetes mellitus in Indonesia is 1.8% in general pregnancy.One of the prevention of diabetes mellitus in pregnancy is sports interventions, including low impact aerobic exercise, such as swimming, jogging and pregnancy exercises. Benefits of pregnancy exercise reduces the risk of gestational obesity.The purpose of this study was to determine the effect of pregnancy exercise on body weight and blood sugar levels of third trimester pregnant women.The type of the study was a quasy experiment with a post test control group design.The study population was all trimester III pregnant women and the sample was 15 people for each intervention group and the control group was taken using a purposive sampling technique. Data collection in the form of weight measurements after pregnancy exercise which is measured 1 time / week for 3 consecutive weeks and measurement of blood sugar levels before and after pregnancy exercise. Bivariate analysis used the Independent T-test and Mann Whitney U. The results showed the influence of pregnancy exercises on body weight (p-value 0.04,) and there was no effect of pregnancy exercises on decreasing maternal blood sugar levels (p-value 0.404). It is recommended for midwives to socialize and improve health services, namely pregnancy exercises for pregnant women regularly and periodically, and provide counseling about the benefits and effects of pregnancy exercises on weight and blood sugar levels of third trimester pregnant women.